An investigation into the feasibility of normal and fibre-reinforced ultra-high performance concrete multi-cell and composite sandwich panels. (September 2021) - Mahdi, S.; Ali, M.S. Mohamed; Sheikh, A.H.; Elchalakani, M.; Xie, T.
Abstract: Inspired by the concept of box girders and bubble deck systems, the present study investigates and develops new forms of composite structures and their behaviours are investigated. The sandwich system implements two basalt fibre-reinforced polymer (BFRP) mesh reinforced ultra-high performance concrete (UHPC) plates as face sheets and a combination of normal strength mortar (NSM) and expanded Polystyrene (EPS) foam as core layers in varying configurations. The box-cell system is produced by UHPC cast into galvanised steel roofing sheet profiles with anchor screws and EPS foam positioned in-situ to produce a box-celled panel. Both systems have three variations for which the structural responses of these panels as one-way slabs under three-point flexure are studied. In addition to the experimental investigations, the sandwich panel theory (EST), advanced sandwich theory (AST), segmental sectional analysis and finite-element analysis are applied to predict the behaviour of the panels at their serviceability limit states. The findings indicate that partially replacing the core with EPS in the sandwich system can effectively reduce the self-weight of the slab without compromising its load capacity under flexure. Moreover, the box-cell system is the most effective when steel fibres are added to the UHPC mix by increasing ductility and preventing early delamination of the steel profile from the UHPC. The modified EST, AST, and sectional analysis can successfully simulate the behaviour of the composite panels within their linear elastic material conditions and the finite-element analysis can accurately model the full-range behaviour of the box-cell composite panels. Highlights: New form of ultra-high performance concrete one-way panels inspired by box-cell and BubbleDeck systems developed. BubbleDeck inspired sandwich panel system has high self-weight to resistance ratio for mortar-foam hybrid core. BFRP-concrete plate provides significant strength in the tensile region when encasing sandwich panels. Box-cell panel system has high ductility and flexural strength when including fibres in concrete mix. Screw anchors provide high resistance as shear connectors when placed through perforated steel profiles for composite panels.